Interleukin-10 Modulates Proinflammatory Cytokines in the Human Monocytic Cell Line THP-1 Stimulated with Borrelia burgdorferi Lipoproteins - Murthy, P. K. (American Society for Microbiology, 2000)
We determined previously that lipoproteins of Borrelia burgdorferi stimulate inflammatory and anti-inflammatory cytokines (interleukin-10 [IL-10]) in monocytes. IL-10 could have an effect on innate and acquired immune responses to B. burgdorferi and influence the magnitude of the infectious inoculum and disease outcome. To understand the mechanism(s) of IL-10 action during early infection, when innate immunity expressed chiefly by skin macrophages is key, we investigated the effect of exogenous and endogenous IL-10 on the production of the macrophage-derived cytokines IL-6, IL-1β, IL-12, and tumor necrosis factor alpha (TNF-α). We used the THP-1 human monocytic cell line and recombinant lipidated OspA (L-OspA) as the model target cell and stimulant, respectively. To determine the kinetics of cytokine production by THP-1 cells, we stimulated them with L-OspA and also with heat-killed B. burgdorferi cells (HBb) and lipopolysaccharide (LPS). Exogenous IL-10 dampened production of inflammatory cytokines, as elicited by lipoproteins. The inhibition of endogenous IL-10 function by anti-IL-10 antibody reduced the production of IL-12 and IL-6 but not that of IL-1β and TNF-α. An inspection of the kinetics of cytokine production clarified this finding. TNF-α was produced prior to, and IL-β was produced at the same time as, IL-10, whereas IL-6 and IL-12 were produced later. HBb, LPS, and L-OspA yielded similar kinetics of cytokine production. This result reinforces the notion that lipoproteins are the functional molecules in HBb and perhaps in vivo. It indicates also that signaling pathways utilized by LPS and lipoproteins may be extensively shared. The results are consistent with a major role played by IL-10 in controlling the initial phase of infection with this spirochete.